2022
DOI: 10.2147/copd.s346456
|View full text |Cite
|
Sign up to set email alerts
|

Different Smoking Statuses on Survival and Emphysema in Patients with Acute Exacerbation of Chronic Obstructive Pulmonary Disease

Abstract: Objective To investigate the association between different smoking statuses and survival and emphysema in patients with acute exacerbation of chronic obstructive pulmonary disease (AECOPD). Methods This retrospective study included patients admitted from October 2014 to September 2017. Demographic, clinical, laboratory, imaging, impulse oscillometry, and traditional pulmonary function data were collected. The relationship between smoking and EI was analyzed via binary l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 21 publications
1
20
0
Order By: Relevance
“…Another smoking status-associated clinical characteristic is emphysema, with a higher prevalence of emphysema in smokers than in non-smokers in AECOPD. This result is in line with findings from a very recent study, in which Ding et al demonstrated that smokers in AECOPD exhibit more severe diffuse dysfunction than never smokers and cigarette smoking represents an independent risk factor for emphysema ( 13 ). In COPD, emphysema is a consequence of chronic inflammatory and consequent destructive processes.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Another smoking status-associated clinical characteristic is emphysema, with a higher prevalence of emphysema in smokers than in non-smokers in AECOPD. This result is in line with findings from a very recent study, in which Ding et al demonstrated that smokers in AECOPD exhibit more severe diffuse dysfunction than never smokers and cigarette smoking represents an independent risk factor for emphysema ( 13 ). In COPD, emphysema is a consequence of chronic inflammatory and consequent destructive processes.…”
Section: Discussionsupporting
confidence: 92%
“…in the same way. In contrast to stable COPD, the association of smoking status with clinical and laboratory phenotypes in patients with AECOPD has only been investigated in few studies with small sample sizes (13,14). In the present study, we aimed to determine the effect of smoking status on demographic, clinical, and laboratory characteristics of AECOPD in a large clinical cohort consisting of 1,034 patients.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…These 28 articles were downloaded and thoroughly reviewed the full text, excluding 10 articles with insufficient data and overlapping studies, leaving 18 articles Finally, 18 articles covering 24 studies were included. [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] The literature selection process is outlined in Figure 1.…”
Section: Literature Retrieval and Inclusionmentioning
confidence: 99%
“…Of the 18 included published papers, [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] involving 24 studies containing a total of 1577 COPD patients and 1436 healthy individuals, including 308 acute COPD and 1269 stable COPD patients. The basic information on the included literature is shown in Tables 1 and 2.…”
Section: Literature Quality and Attributesmentioning
confidence: 99%